EVALUATION OF THE PANGANDARAN DISTRICT BPBD POLICY IN DISASTER RISK REDUCTION EFFORTS IN PANGANDARAN DISTRICT - Arjuna Arief Kesuma; Ixora Lundia Suwaryono (Laboratorium Administrasi Publik FISIP Universitas Andalas, 2024)
This study assesses the performance of the Regional Disaster Management Agency (BPBD) in Pangandaran Regency by analyzing its policies and reviewing disaster reduction reports. Utilizing a literature review method, with a focus on BPBD Pangandaran Regency's policy documents, the evaluation links the Strategic Plan (Renstra) to outcomes in the Performance Accountability Report (LAKIP). The Renstra outlines disaster prevention, emergency response, and post-disaster policies, translated into programs to enhance the region's disaster management capacity, measured by the Regional Resilience Index. Despite an improved index attributed to successful handling of 125 disasters in 2022, including fires, tornadoes, landslides, floods, and earthquakes, the study notes challenges such as a lack of updates in crucial documents and insufficient human resources impacting BPBD Pangandaran's performance. While the agency has achieved a 100% performance realization in various programs, attention to document updates and resource allocation is essential for more efficient disaster management in Pangandaran Regency.